Associated Factors and Outcome of Uterine Rupture at Suhul General Hospital, Shire Town, North West Tigray, Ethiopia 2016: A Case-Control Study - Tefera Marie Bereka; Amlaku Mulat Aweke; Tewodrose Eshetie Wondie (Obstetrics and Gynecology International)
Background. Uterine rupture is tearing of the uterine wall during pregnancy or delivery. It may extend to partial or whole thickness of the uterine wall. It is usually a case where obstetric care is poor. In extensive damage, death of the baby and sometimes even maternal death are evident. Objective. This study assesses associated factors and outcome of uterine rupture at Suhul General Hospital, Tigray Region, Ethiopia, 2016. Methodology. A case-control study was conducted by review of data from September 2012 to August 2016. A total of 336 samples were studied after calculating by EPI-INFO using proportion of multiparity (53%) and ratio of 1 : 2 for cases and controls, respectively. Analysis was done using SPSS version 20. Bivariate and multivariate logistic regression was applied with p<0.05. Result. ANC, grand multiparity, malpresentation, and obstructed labor had association, but previous cesarean delivery was not significant. Perinatal mortality was 105 (93%) versus 13 (5.8%) in cases and controls, respectively. Anemia was highest for both groups (53.7% versus 32.1%). Conclusion. Majority of uterine rupture is attributed to prolonged or obstructed labor. Cases of uterine rupture had prompt management preventing maternal mortality, but burden of perinatal death is still high.